2009
DOI: 10.1007/s11274-009-0275-0
|View full text |Cite
|
Sign up to set email alerts
|

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent

Abstract: The discharge of textile wastewater containing dye in the environment is varying for both toxicology and esthetical reasons as dyes impede light penetration, damage the quality of the receiving streams. Upflow anaerobic sludge blanket reactor with anaerobic digester sludge treating starch wastewater has been used to investigate the removal efficiency of chemical oxygen demand (COD) and colour of textile dye wastewater. In this study, the starch and textile dye wastewater was mixed at 70 and 30%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…G. Gnanapragasam и др. [59] изучали очистку текстильных сточных вод в иловом реакторе выше по течению. При 6,81 кг ХПК/м 3 /сут.…”
Section: таблица 2 сравнение методов удаления красителей из сточных водunclassified
“…G. Gnanapragasam и др. [59] изучали очистку текстильных сточных вод в иловом реакторе выше по течению. При 6,81 кг ХПК/м 3 /сут.…”
Section: таблица 2 сравнение методов удаления красителей из сточных водunclassified
“…It is important to mention that hydrolytic and fermentative bacteria may play an important role during the anaerobic treatment of textile wastewaters because this kind of effluents contain different polymers, such as starch, which are utilized during the production of fabrics (Dos Santos et al 2006a). In fact, high decolourisation efficiencies have been achieved in anaerobic bioreactors in which starch and carboxymethyl cellulose have been used as energy source (Isik and Sponza 2008;Gnanapragasam et al 2010). Recent experiments documented in detail the role of glucose-fermenting bacteria on the reductive decolourisation of azo dyes.…”
Section: Fermentative and Methanogenic Microorganismsmentioning
confidence: 99%
“…Biogas production in relation to COD is about 0.4 m 3 /kg COD removed, corresponding to a methane production of 0.35 m 3 CH 4 per kilogramme of COD removed. Biogas production is directly related to COD stabilization, for example without biogas production minimal COD removal occurs (Grady et al 1999). Gnanapragasam et al (2010) had reported the maximum production of biogas was about 355 L/day at 24 h of HRT by recycling the treated wastewater.…”
Section: Biogasmentioning
confidence: 99%